Evaluation of Front Line Demonstrations on Summer Moong (Vigna radiata) in Sangrur district of Punjab (Indian Journal of Extension Education, 2020)
The study was conducted with an objective of enhancing farmers’ income through crop intensification. A total of 175 front line demonstrations were conducted on summer moong (Vigna radiata) var. SML 668, during year 2017 and 2018 and SML 832 during year 2019 in two adopted villages of Sangrur district under Farmer FIRST Project. During the year 2017, a yield of 10.84 q/ha and 9.38 q/ha was obtained in FLD plots and local checks respectively. During 2018 and 2019, average yield of 10.25 q/ha and 10.30 q/ha was obtained in FLD plots as compared to 9.30 q/ha and 9.02 q/ha respectively in local check plots. Cost of cultivation of the summer moong at demonstrated field was Rs. 17918.57/ha whereas it was 16687.85/ha in case of farmers’ fields during 2017 and net returns of the demonstrated field and local check were Rs. 38720.43/ha and Rs. 32322.64/ha respectively. The B:C ratio of the demonstrated and local check were 3.16 and 2.94 respectively. In 2018 BC ratio of 2.96 and 2.71 was obtained in FLDs and check plots and during 2019 BC ratio of 2.94 and 2.44 was obtained in FLDs and check plots respectively. Farmers were unaware about the appropriate time of application and adequate dose of the pesticides.